Performance Optimization in Lead-Free Perovskite Solar Cell: A Comparative Approach - Aisha Shaikh (22330846) (2025)
Perovskite solar cells (PSCs) technology posses potential among numerous solar cells due to their promising sustainable energy solutions. However, commercial viability of lead-based perovskites is challenging due to its toxicity and stability challenges. Tin-based perovskites have shown up as a lead-free, comparatively excellent alternative, but the efficiency and stability of tin perovskites needs further optimization. In this study, formamidinium tin-based PSC was simulated using SCAPS-1D and optimized key architectural characteristics such as thickness, doping concentration, bandgap, and electron affinity of the absorber and charge transport layers. The effect of these changes on efficiency was examined, and the experimental outcomes were compared with existing literature to determine optimal parameters. These optimal variations in the architecture depicts optimal parameters such as open-circuit voltage of 0.764 V, a short-circuit current density of 25.28 mA/cm2, a fill factor of 73.26% and a PCE of 14.17%. A thicker absorber layer combined with optimization of the charge transport layers resulted in reduced charge recombination losses. Further improvements in the bandgap and electron affinity led to better energy-level alignment and improved performance. This paper illustrates that careful optimization of the architectural parameters can lead to a significant enhancement in the efficiency of PSC for tin. These studies are essential for developing efficient, non-toxic and potentially scalable lead-free solar cells. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2025.3543244